Impact of Bacterial Metabolites on Gut Barrier Function and Host Immunity: A Focus on Bacterial Metabolism and Its Relevance for Intestinal Inflammation - Gasaly, Naschla; de Vos, Paul; Hermoso, Marcela A. (Frontiers in Immunology, 2021)
The diverse and dynamic microbial community of the human gastrointestinal tract plays a vital role in health, with gut microbiota supporting the development and function of the gut immune barrier. Crosstalk between microbiota-gut epithelium and the gut immune system determine the individual health status, and any crosstalk disturbance may lead to chronic intestinal conditions, such as inflammatory bowel diseases (IBD) and celiac disease. Microbiota-derived metabolites are crucial mediators of host-microbial interactions. Some beneficially affect host physiology such as short-chain fatty acids (SCFAs) and secondary bile acids. Also, tryptophan catabolites determine immune responses such as through binding to the aryl hydrocarbon receptor (AhR). AhR is abundantly present at mucosal surfaces and when activated enhances intestinal epithelial barrier function as well as regulatory immune responses. Exogenous diet-derived indoles (tryptophan) are a major source of endogenous AhR ligand precursors and together with SCFAs and secondary bile acids regulate inflammation by lowering stress in epithelium and gut immunity, and in IBD, AhR expression is downregulated together with tryptophan metabolites. Here, we present an overview of host microbiota-epithelium- gut immunity crosstalk and review how microbial-derived metabolites contribute to host immune homeostasis. Also, we discuss the therapeutic potential of bacterial catabolites for IBD and how essential dietary components such as dietary fibers and bacterial tryptophan catabolites may contribute to intestinal and systemic homeostasis.